2009
DOI: 10.1144/sp327.2
|View full text |Cite
|
Sign up to set email alerts
|

Caldera volcanism and rift structure in the Taupo Volcanic Zone, New Zealand

Abstract: The Taupo Volcanic Zone (TVZ) is an active continental volcanic arc/back-arc basin in central North Island, New Zealand. It is the youngest area of volcanic activity that extends southwards from the Coromandel Volcanic Zone (CVZ), where andesitic volcanism began c. 18 Ma and rhyolitic volcanism c. 10 Ma. It is an extensional basin (average c. 8 mm a 21 ) with numerous, predominantly normal (dip .608) faults within the Taupo Rift, but with some strike-slip component. TVZ can be divided into three parts. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…1: Wilson et al, 1995;Rowland and Sibson, 2001), and in its modern form coincides with a structurally and magmatically segmented rift system (Taupo rift). The oblique subduction of oceanic crust from the Pacific plate beneath the Indian-Australian plate caused the back arc/arc basin producing the TVZ (Cole, 1990;Bibby et al, 1995Bibby et al, , 2008Darby et al, 2000;Rowland and Sibson, 2004;Cole and Spinks, 2009;Seebeck et al, 2010;.…”
Section: Geological Settingmentioning
confidence: 99%
“…1: Wilson et al, 1995;Rowland and Sibson, 2001), and in its modern form coincides with a structurally and magmatically segmented rift system (Taupo rift). The oblique subduction of oceanic crust from the Pacific plate beneath the Indian-Australian plate caused the back arc/arc basin producing the TVZ (Cole, 1990;Bibby et al, 1995Bibby et al, , 2008Darby et al, 2000;Rowland and Sibson, 2004;Cole and Spinks, 2009;Seebeck et al, 2010;.…”
Section: Geological Settingmentioning
confidence: 99%
“…Such maps have already been produced for volcanic areas such as Etna volcano (Sicily, Italy) (Azzarro, Branca, Gwinner, & Coltelli, 2012), Taupo Volcanic Zone (New Zealand) (Cole & Spinks, 2009), TeideCañadas (Tenerife, Canary Islands, Spain) (Galindo, 2005), or La Garrotxa Volcanic Field (Catalonia, Spain) (Bolós et al, 2015). Under the same theme, the study presented here aims at identifying, mapping, and interpreting the main volcano-structural elements of El Hierro (Canary Islands, Spain; Figure 1), in both submarine and subaerial parts of the volcanic edifice.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature data given by Leaver (2006) are the inferred average temperatures in the 3 km Wilson et al (1995) and Kissling and Weir (2005). (b) Calderas shown by Kissling and Weir (2005) and Cole and Spinks (2009). Black dashed lines are maximum extent of calderas, black solid lines are possible structural boundaries and purple lines are volcanic centres stated in Kissling and Weir (2005) and within this paper.…”
Section: Available Heat Output Mass Flow Rates and Temperature Informentioning
confidence: 91%
“…Black dashed lines in these figures show the maximum extent of calderas described by Wilson et al (1995) in Fig. 4a and Cole and Spinks (2009) in Fig. 4b, while the volcanic centre boundaries stated in Kissling and Weir (2005) and used in this modelling study are shown with purple lines in both Fig.…”
Section: Geology and Permeabilitiesmentioning
confidence: 99%